STRATEGI PENGEMBANGAN OBJEK WISATA DANAU LINOUW TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KOTA TOMOHON - Ireyne Olivia Eman; Benny Adrian Berthy Sagay; Sherly Gladys Jocom (AGRI-SOSIOEKONOMI, 2018)
The purpose of this study are to know about strategys to development tourism object Danau Linouw to increasing local revenue of Tomohon City. This study use descriptive qualitative method. The sampling technique is taken based on the consideration that the existing population is not known exactly in number so using accidental sampling. The variables in this study consisted of the development of tourist attraction and the increase of local revenue (PAD). Data collection techniques consist of interviews, observation, questionnaires, documentation. Data analysis techniques use SWOT analysis and development strategy. The result of the research shows that the development strategy of Lake Linouw Tourism Object in increasing Tomohon District Revenue (PAD) based on SWOT analysis has been done, located in Quadrant I position or strategy through Horizontal Integration, which is located between external opportunity and internal strength. This is a major strategy for developing tourism by maintaining strength and optimizing opportunities while improving weaknesses and anticipating existing threats in an effort to increase the number of tourist arrivals that can increase local revenue (PAD) of Tomohon City. To increase the original revenue of Tomohon City, it is hoped that the Government and Private sector, especially Lake Linouw Tourism Manager, need to plan a marketing strategy so that tourists who visit will continue to grow. Improving facilities and infrastructure related to access road to Lake Linouw attraction which is considered less extensive to be passed by visitors who use motor vehicles.